Strategi Pendampingan Hafalan Al Qur'an Anak Tunarungu di Pesantren Daarul Ashom - Faishal Abyan; Difa'ul Husna (Program Pascasarjana UNU Surakarta, 2023)
This study discusses strategies and supporting and inhibiting factors in assisting deaf children in memorizing the Qur'an at the Daarul Ashom Islamic boarding school. The research method is in the form of qualitative descriptive research by conducting interviews, observation, and documentation in knowing field data. In this study, three main analysis techniques were used, namely data reduction, data presentation, and conclusion. The results of the study show that: 1. The strategy for assisting the memorization of the Qur'an for deaf children at the Daarul Ashom Islamic boarding school uses the Hijaiah Letter Signing method. pre-tahfiz activities intended for Daarul Ashom students to learn hijaiah letter signs, the process of memorizing at the Daarul Ashom Islamic boarding school with signs and writing. freeing the success of the attack, namely the students' ability in symbolizing and writing hijaiah letters 2. The supporting factors in assisting the memorization of the Qur'an for deaf children at the Daarul Ashom Islamic boarding school are competent teachers or Ustaz, consistency in using one mushaf, and a conducive environment. The inhibiting factors in mentoring the memorization of the Qur'an for deaf children at the Daarul Ashom Islamic boarding school are the limitations of the ustaz, articulation, and space for learning activities.